Formulation, Stability and Effect of Storage on the Quality of Three Artificial Feeds used in Carp Culture - H., Shivananda Murthy; K.V., Devaraj (Fishery Technology, 2025)
Three artificial feeds namely, EF, PF and SF incorporating leaf powders of Eichhornia, Pistia and Salvinia respectively were formulated and compared with conventional feed (CF) for their water stability and keeping quality. After 1 h in water PF was found more stable than other feeds. The moisture content increased in all the feeds by 4 months storage and all the feeds showed the same keeping quality.